2004
DOI: 10.1207/s15327558ijbm1101_6
|View full text |Cite
|
Sign up to set email alerts
|

The role of spirituality in the psychological adjustment to cancer: A test of the transactional model of stress and coping

Abstract: Recent studies in the oncology literature have shown that spirituality, defined as the combination of existential and religious well-being (RWB), is related to both emotional well-being and quality of life. Indeed, spirituality may be particularly important in coping with the potential life threat of the disease. Based on Frankl's (1963) existential theory, in this study, we examined whether the relations between spirituality and emotional well-being are moderated by degree of perceived life threat (PLT). In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
108
0
7

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(126 citation statements)
references
References 31 publications
11
108
0
7
Order By: Relevance
“…A positive association between overall SpWB and QOL remained significant after controlling for demographic and clinical variables 14,[20][21][22]32,34,36,43 with the exception of one study 44 (see Table 3). However, this positive association (ranges from 0.36 to 0.70) was not equal when QOL was broken down into its physical (ranges from 0.22 to 0.54), social (ranges from 0.24 to 0.54), emotional (ranges from 0.27 to 0.58), and functional dimensions (ranges from 0.38 to 0.67).…”
Section: Sample and Ethodological Characteristicsmentioning
confidence: 92%
See 2 more Smart Citations
“…A positive association between overall SpWB and QOL remained significant after controlling for demographic and clinical variables 14,[20][21][22]32,34,36,43 with the exception of one study 44 (see Table 3). However, this positive association (ranges from 0.36 to 0.70) was not equal when QOL was broken down into its physical (ranges from 0.22 to 0.54), social (ranges from 0.24 to 0.54), emotional (ranges from 0.27 to 0.58), and functional dimensions (ranges from 0.38 to 0.67).…”
Section: Sample and Ethodological Characteristicsmentioning
confidence: 92%
“…Existential well-being measured as one subscale of the MQOL strongly correlated with a single-item scale measuring overall QOL and moderately correlated to the selfadministered Spitzer Quality of Life Index (SA-QLI). 28 Laubmeier and colleagues 43 identified a positive association between existential well-being (measured on the SWBS) and overall QOL. Johnson and colleagues 46 reported that global meaning measured on LAP-R PMI was positively associated with mental health (on the SF-36).…”
Section: Sf-36 Facit-sp-12mentioning
confidence: 99%
See 1 more Smart Citation
“…The literature indicates that spiritual concerns are important to quality of life and health among cancer patients, and that spirituality facilitates cancer coping [13][14]. It has been suggested that spirituality be a focus of models addressing quality of life in oncology patients [15].…”
Section: Role Of Spirituality In Cancer Copingmentioning
confidence: 99%
“…This finding confirmed the view of Levin and Schiller (1987) that the development of intrinsically orientated religious variables and positive psychological attitudes may buffer individuals from stress-related components of illness. Laubmeier, Zakowski and Bair (2004) found that spirituality (which they define as a combination of existential and religious well-being), was related to both emotional well-being and quality of life. In a study conducted in Chicago, United States of America, on 95 cancer patients with various types of cancer, they found that spirituality (especially the existential component) was associated with reduced symptoms of distress and better quality of life, regardless of life threat.…”
Section: International Studies Focusing On Spiritual Well-beingmentioning
confidence: 99%